Pemanfaatan Radio Kampus sebagai Media Pembelajaran dengan Unsur Islami - Primadi Fajriansyah Nawawi; Endri Listiani (Bandung Conference Series: Communication Management, 2023)
Abstract. The background of this research is because radio is primarily a place to get information and entertainment in a monotonous form. The 24 Stations, which call themselves campus radio, are present in the surrounding community to support lecture processes that require direct applications with the aim of facilitating students at the Unisba Faculty of Communication Sciences. This study discusses the Utilization of Campus Radio as Learning Media in Islamic Elements. The research objective is to describe the students' use of radio as a learning medium and Islamic elements. To reveal these issues, thoroughly and in depth, researchers use a qualitative research approach. Then the data were analyzed critically with the theory of Encoding and Decoding which is linked to learning Islamic elements so as to obtain a deep meaning of reception analysis. The research method used by the authors in this study is qualitative with a research approach, namely audience reception analysis through open interview techniques, observation, literature studies, and documents relevant to research, this research uses data analysis techniques, data presentation, data reduction, data analysis and data withdrawal. the conclusion of the subject of this study is the audience or listeners of The 24 Station Radio Unisba while for the supporting informant is Ahmad Fadli as laboratory assistant and station manager of The 24 Station Radio Unisba. From the research results, the audience's understanding of radio as a learning medium, as well as the use of Islamic elements in its content and packaging. Audiences receive Islamic elements of learning from the form of learning media provided by The 24 Station. Adjust to the circumstances of each culture, social position and circumstances of each audience. Abstrak. Penelitian ini dilatar belakangi, karena radio utamanya merupakan wadah mendapatkan informasi dan hiburan yang bentuknya monoton. The 24 Stations yang menyebutkan diri sebagai radio kampus hadir dalam masyarkat sekitarnya untuk mendukung proses perkuliahan yang membutuhkan aplikasi secara langsung dengan tujuan mempermudah mahasiswa di Fakultas Ilmu Komunkasi Unisba. Penelitian ini membahas tentang Pemanfaatan Radio Kampus sebagai Media Pembelajaran dalam Unsur Islami. Tujuan penelitian yaitu untuk mendeskripsikan mengenai pemanfataan mahasiswa terhadap radio sebagai media pembelajaran dama unsur islami. Untuk mengungkapkan persoalan tersebut, secara menyeluruh dan mendalam, peneliti menggunakan pendekatan penelitian kualitatif. Kemudian data dianalisis secara kritis dengan teori Encoding dan Decoding yang dikaitkan pada pembelajaran unsur islami sehingga memperoleh makna yang mendalam tentang analisis resepsi. Metode penelitian yang penulis gunakan pada penelitian ini adalah kualitatif dengan pendekatan penelitian yaitu analisis resepsi audiens melalui teknik wawancara terbuka, observasi, studi literatur, dan dokumen yang relevan dengan penelitian, penelitian ini menggunakan teknik analisis data, penyajian data, reduksi data analisis data dan penarikan kesimpulan subjek dari penelitian ini yaitu audiens atau pendengar dari The 24 Station Radio Unisba sedangkan untuk narasumber pendukung ialah Ahmad Fadli selaku laboran sekaligus station manager The 24 Station Radio Unisba. Dari hasil penelitian, pemahaman khalayak mengenai radio sebagai media pembelajaran, serta pemanfaatan unsur islami dalam isi dan kemasannya. Audiens menerima pembelajaran unsur islami dari bentuk media pembelajaran yang diberikan oleh The 24 Station. Menyesuaikan dengan keadaan budaya masing-masing, posisi sosial dan keadaan masing-masing audiens.